Psychological Analysis on the Issues of Violence Against Women in Language and Media - Ilman Nafi'a; Septi Gumiandari (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
Language and media are effective entities to perpetuate male domination over women. Both are representations of various social conflicts, interests, power and hegemony. Through Psychological analysis, this study aims to reveal how both of them can establish the process of 'marginalizing' women. This study used a qualitative method with a literature review approach. The results showed that violence against women in language and the media is an invisible form of violence. Language is something that has a purpose (teleology) in itself, which is conditioned by various environmental interests. In patriarchal culture, language is used to build a bad image of women with the aim of strengthening the position of men as the dominant group. The bad image is then transplanted by the media, made into a universe of discourse and implanted into collective consciousness as the public's subconscious imagination. As a result, whether we realize it or not, women are treated in a subordinate way, but also define themselves in a subordinate way according to men's eyes. Bahasa dan media adalah entitas yang efektif untuk mengekalkan dominasi laki-laki atas perempuan. Keduanya merupakan representasi dari pagelaran berbagai konflik sosial, kepentingan, kekuasaan serta hegemoni. Melalui analisis Psikologi, kajian ini bertujuan untuk mengungkapbagaimana keduanya dapat memapankan proses ‘memarjinalkan’ kaum perempuan. Kajian ini menggunakan metode kualitatif deskriptif dengan teknik pengambilan data sekunder melalui kajian literatur. Hasil penelitian menunjukan bahwa kekerasan terhadap perempuan dalam bahasa dan media adalah bentuk kekerasan yang tidak kasat mata. Bahasa merupakan ekspresi seseorang untuk mewakili logika, struktur budaya, sosial, psikologi, filosofi, dan politik yang dianut oleh penuturnya. Ia memiliki ketertujuan (teleologi) di dalam dirinya, yang terkondisi oleh pelbagai interes lingkungannya. Dalam budaya patriarkhi, Bahasa digunakan untuk membagun image buruk pada perempuan dengan tujuan mengukuhkan posisi laki-laki sebagai kelompok dominan. Image buruk tersebut kemudian dicangkok oleh media, dijadikan pemahaman universal, dan ditanamkan ke dalam kesadaran kolektif sebagai imajinasi alam bawah sadar masyarakat. Wal-hasil, disadari atau tidak, perempuan selain diperlakukan secara subordinatif, juga mendefinisikan diri secara subordinatif sesuai dengan perspektif laki-laki.